Retrospective Analysis of Penicillin G Minimum Inhibitory Concentration for Gram-Positive Isolates of Non-Severe Clinical Mastitis - Stefanie Leimbach; Franziska Nankemann; Anne Tellen; Doris Klocke; Nicole Wente; Yanchao Zhang; Volker Krömker (Antibiotics)
Background: Despite penicillin having a longstanding reputation as being scientifically approved for the treatment of bovine mastitis, its market share and practical application rate seem rather low. While in some countries, cases of mild and moderate mastitis are treated almost completely with simple penicillin, in other countries, penicillin is rarely used as a mono-substance in udder tubes. Methods: Based on minimal inhibitory concentration (MIC) studies of 1489 isolates of Gram-positive microorganisms isolated from bovine mastitis cases, the extent to which penicillin preparations can fulfil their role as first-line treatment and in how many cases insufficient efficacy must be assumed was assessed in comparison with more recent studies on the achievable levels of active substances in milk. Results: Of the isolates, 76% had an MIC of ≤0.125 µg/mL and 95% of the isolates had an MIC of ≤1 µg/mL. Conclusions: The data show that in Northern Germany, it can be assumed that penicillin is a good choice in most cases of mastitis caused by Gram-positive mastitis pathogens, at least from the perspective of antibiotic resistance.